EFFECTIVENESS OF THE PLASTIBELL CIRCUMCISION IN NEONATESAND INFANTS AT A TERTIARY CARE HOSPITAL - Muhammad Abid Owais (Baqai Journal of Health Sciences)
ABSTRACT Objective: Circumcision is the most frequently performed surgery in neonates and infants across the globe. The objective of this study was to assess the effectiveness of circumcision performed by Plastibell method by means of its safety and complications in neonates and infants. Methods: This prospective study was carried out in the department of surgical sciences, Baqai medical university on 480 male neonates and infants who were circumcised with plastibell technique during January 2017 to November 2019. Data were collected on a set proforma indicating age of the patient, plastibell size, time required by the device to detach and complications. Children were divided into two arms; neonates (0 to 4 weeks) and infants (5weeks to 1year). On discharge parents were instructed about the care of the device and were asked to follow up on day 3 and on day of detachment of Plastibell. Results: During our study period, we included and evaluated 480 cases of circumcision by plastibell method. Out of these 480 cases, 198 (41.25%) were neonates, while the rest of 282 (58.75%) were infants. Majority of the cases 429 (89.38%) showed no complications. Amongst these, 258/282 (91.49%) were infants whereas 171/198 (86.36%) were neonates. A small number of patients 51 (10.63%) presented with trivial complications. In infants, among 198 cases, 27 (13.64%) presented with complications whereas, in neonates, only 24 (8.51%) out of 282 complications. Conclusion: The disparity in the frequencies of complications amongst infants and neonates is negligible. Hence, the dissimilarity of age in neonates and infants does not affect the usefulness of Plastibell technique and proves it secure and comparable in its result. Therefore, we can say that a circumcision done by appropriate Plastibell technique gives acceptable results and can be performed even in a year-old child and emends the doubtfulness in the minds of surgeons.